The economic prospects of the CIS : sources of long term growth - Ofer, Gur.; Pomfret, Richard W. T. (Cheltenham, UK ; Northhampton, MA : Edward Elgar Pub., 2004)
This book brings together ten original studies on the transition and growth experience and the foundations for long-term growth of the newly independent states created by the dissolution of the Soviet Union.
Includes bibliographical references (p. 276-287) and index.
osc 31/8/16
Loans
Keywords: Economic growth; Economic conditions; Former Soviet republics